The Role of The Board of Directors Characteristics on Financial Performance Mediated by The Corporate Reputation - Mardiana, Ana; Holly, Anthony; Jao, Robert (Contemporary Journal on Business and Accounting, 2024)
Purpose – this study is to analyze the effect of the number of directors (consisting of the proportion of women on board, the size of directors and the presence of foreign directors) Design/methodology/approach – This study uses the theory of resource dependence. This study used purposive sampling method and in the sample pelicans used secondary data Findings – The results of this study indicate that the proportion of women in the board of directors is positive. The size of the Sukum board of directors has a significant positive effect on the company's reputation. The power of the foreign advisory board is a significant positive impact on reputational damage. This research shows that the company's reputation is not good for the company's reputation. the role of the company's reputation is able to mediate the need between the foreign board of directors and the company's financial persuasive persuasion Originality – The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) with a research period of 2019-2021 Keywords : Company Reputation, Characteristics of the Board of Directors, Financial Performance Paper Type : Research Result